Multimodal Networks of Signs between Language, Body and World in Poetry, Music and Architecture in the City of Valencia (Spain) (Signifiances (Signifying), 2024)
This work will deal with the sign networks that are established between language and world in the work of semiotic different arts (poetry, music and architecture). The objective is to understand and analyze from Enaction theory and from the Semiotic sign of Peirce how the constant flow and ebb between social environment, body and language configure both language and the world. It will also be shown how the work of art constitutes an emergency in which language, body and social environment participate. To achieve these objectives, poetic texts by the Valencian author Ausiàs March and artistic works related to them will be analyzed. The work methodology includes sign analysis, the comparison of original texts with translations and the comparison of works of art of semiotic different kinds.Dans ce travail, seront abordés les réseaux de signes qui s’établissent entre le langage et le monde dans l’œuvre d’art. L’objectif est de comprendre et d’analyser à partir de la théorie de l’énaction et de la sémiotique comment le flux et le reflux constants entre l’environnement social, le corps et le langage configurent à la fois le langage et le monde. Il sera également montré comment l’œuvre d’art constitue une urgence à laquelle participent le langage, le corps et l’environnement social. Pour atteindre ces objectifs, seront analysés les textes poétiques de l’auteur valencien Ausiàs March et les œuvres artistiques qui y sont liées. La méthodologie de travail comprend l’analyse des signes, la comparaison de textes originaux avec des traductions et la comparaison d’œuvres d’art de toutes sortes.